Flexible and reversibly deformable radio-frequency antenna based on stretchable SWCNTs/PANI/Lycra conductive fabric. (18th September 2017) - Guo, Xiaohui; Huang, Ying; Wu, Can; Mao, Leidong; Wang, Yue; Xie, Zhicheng; Liu, Caixia; Zhang, Yugang
Abstract: We demonstrated a flexible and reversibly deformable radio-frequency antenna based on SWCNTs/PANI/Lycra conductive fabric and semipermeable film for wireless wearable communications applications. The conductive fabric fabricated by using the 'dip and dry' process exhibits good flexibility, electrical stability, stretchability and mechanical properties, and a high electrical conductivity (with low sheet resistance of ∼35 Ω/sq) was obtained based on the SWCNTs/PANI synergistic conductive network. The morphology of the semipermeable film was investigated to further illustrate the waterproof breathable features. Meanwhile, the modeling, fabrication procedure and radiating properties of the radio-frequency textile antenna worked at 2.45 GHz were systematically illustrated. The measured reflection coefficient, VSWR and the −10 dB bandwidth is ∼−18.6 dB, 1.58 and ∼270 MHz respectively, which agreed well with the simulation results. Furthermore, the results indicate that the design methodology for the radio-frequency textile antenna could have promising applications in flexible and reversibly deformable antennas for wearable wireless communications systems.